Changing the idea of language: Nigel Love's perspective. (May 2017) - Cowley, Stephen J.
Abstract: From Nigel Love's perspective, language is a multi-scalar process that connects people, history and nature. In leaving behind the Saussurian tradition's object based views, he contrasts first and second order language. However, the 'orders' do not explain each other and, implicated as they are in change, cannot be defined. Indeed, Love suggests that language can describe everything under the sun – except language. I concur that how people speak cannot explain language and, conversely, that linguistic analysis cannot explain how people speak. By tracing language to interdependency between two 'orders', Love makes use of carefully crafted tautologies. Such a perspective illustrates the kind of abduction that Gregory Bateson finds across nature. In showing this, I compare how contingency-driven change serves birds with Love's use of beguiling tautologies. These, I claim, contribute much to the productivity of his perspective. While integrationists celebrate his tautologies as paradoxes, in dialogism, there is a tendency to relate them to theses. Others make unexpected changes: the Distributed Language Approach traces language to interactivity between ecological beings and, echoing hylomorphism, others trance human plasticity to the interplay of language, nature and peculiar kind of social agency. As the effects of Love's perspective ripple across the human sciences, I conclude, they are changing the idea of language.